The Effect of Knowledge, Leadership Style and Work Stress on Employee Performance with Innovation as an Intervening Variable: Pengaruh Pengetahuan, Gaya Kepemimpinan dan Stres Kerja terhadap Kinerja Karyawan dengan Inovasi sebagai Variabel Intervening - Kebajikan, Satriyo Gadang; Sumartik, Sumartik (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study was to determine the effect of knowledge, work stress and leadership style on employee performance at UMKM Sumber Rejeki Tanggulangin with innovation as an intervening variable. The type of research is survey research with a quantitative approach. Because the total population is less than 100 or can be said to be a saturated sample, the total sample used is the same as the total population, namely 45 respondents. The data analysis technique used is path analysis. The data collection technique used in this research is to distribute questionnaires and the tool to analyze the data obtained is to use IBM SPSS Statistics 25 for windows. The results obtained from this study prove that 1) Knowledge variable affects innovation at UMKM Sumber Rejeki Tanggulangin 2) Job stress variable affects innovation at UMKM Sumber Rejeki Tanggulangin 3) Leadership Style variable affects Innovation at UMKM Sumber Rejeki Tanggulangin 4) Knowledge variable Affects Employee Performance at UMKM Sumber Rejeki Tanggulangin 5) Work stress variable affects employee performance at UMKM Sumber Rejeki Tanggulangin 6) Variables of Leadership Style affect employee performance at UMKM Sumber Rejeki Tanggulangin 7) Innovation variable affects employee performance at UMKM Sumber Rejeki Tanggulangin 8) Knowledge variable affects employee performance through innovation at UMKM Sumber Rejeki Tanggulangin 9) Variable work stress affects employee performance through innovation at UMKM Sumber Rejeki Tanggulangin 10) Variable leadership style does not will have an effect on employee performance through innovation at UMKM Sumber Rejeki Tanggulangin.